A prospective cohort study of digital cushion and corium thickness, Part 1: associations with body condition, lesion incidence and proximity to calving - Newsome, Reuben; Green, Martin J.; Bell, N.J.; Bollard, N.J.; Mason, C.S.; Whay, H.R.; Huxley, J.N. (American Dairy Science Association, 2017)
Claw horn disruption lesions (CHDL) are a major cause of lameness in dairy cattle and are likely a result of excessive forces being applied to the germinal epithelium that produces claw horn. The digital cushion is a connective tissue structure, containing depots of adipose tissue, that sits beneath the distal phalanx and has been shown to be thicker in fatter cows. Body condition score (BCS) loss is a risk factor for CHDL, and one possible explanation is that fat is mobilised from the digital cushion during negative energy balance, causing the digital cushion to thin and lose force dissipating capacity, leading to disruption of claw horn growth. This prospective cohort study investigated the association between measures of body fat and sole soft tissues (SST) thickness (a combined measure of the corium and digital cushion beneath the distal phalanx) in a longitudinal manner. SST of 179 cows in two high yielding dairy herds were measured at five assessment points between 8 weeks prior to and 35 weeks post calving. BCS, back fat thickness (BFT) and lesion incidence were recorded. Data were analysed in a 4-level mixed effects regression model, with the outcome being SST thickness beneath the flexor tuberosity of the distal phalanx. Data from 827 assessment points were available for analysis. The overall mean of SST was 4.99 mm (SD: 0.95). SST was thickest 8 weeks prior to calving (5.22 mm, SD: 0.91) and thinnest one week post-calving (4.68 mm, SD: 0.87), suggesting that there was an effect of calving on SST. BFT was positively correlated with SST in the model with a small effect size (a 10 mm decrease in BFT corresponded with a 0.13 mm decrease in SST), yet the nadir of BFT was 11.0 mm at 9-17 weeks post calving (when SST was ~4.95 mm), rather than occurring with the nadir of SST immediately after calving. SST also varied with other variables, e.g. cows that developed a sole ulcer or severe sole haemorrhage during the study had thinner SST (-0.24 mm), except when a sole ulcer was present, when it was thicker (+0.53 mm). Cows that developed lesions had a thinner digital cushion prior to the lesion occurrence, which became thickened with sole ulcer presence, perhaps representing inflammation. Further, whilst BFT was correlated with SST over time, SST may also have been influenced by other factors such as integrity of the suspensory apparatus, which could have a major effect on CHDL. Measures of body fat likely contributed to having thin SST, but other factors including calving, herd and lesion presence also had an effect